Lean manufacturing and ergonomics in the metallurgical industry: an integrated approach for performance improvement - Brito, Marlene Ferreira (2021)
Due to an increasingly competive market, most companies can only survive through continuous improvement, by increasing their productivity and reducing costs. The Lean Production System (SPL) is more and more often used for this purpose.However, the workers' well-being is often neglected, leading to musculoskeletal problems and other occupational diseases. Several authors have identified a gap in the literature regarding the identification of the best practices in the integration of the prevention of musculoskeletal diseases in an SPL. The main objective of this thesis is to clarify the relationship between Ergonomics and LPS and provide the necessary tools for practitioners to implement an ergonomic LPS in their production areas. To achieve this objective, a systematic review was performed and case studies were conducted in four production areas in a metallurgical company using Lean concepts, ergonomic analysis and simulation. From the results found in the literature, which were validated by the four case studies, we can conclude that the integration of Ergonomics during an SPL implementation has the potential to result in gains in productivity and simultaneously improve working conditions. To potentiate these results, several components must be taken into account, namely: the integration of ergonomics in the design of the workstation, the tools for monitoring and evaluation, training and the automation of the manual tasks. Beyond the results obtained and the lessons learned from the case studies, two important tools were developed and validated which were a great support to the implementation of future studies in different areas or sectors: the methodology flowchart and ErgoSafeCI (a tool to evaluate and monitor the LPS implementation while taking into account the ergonomic and safety aspects of a production area). This work offers a valuable contribution for researchers and professionals because it demonstrates how the integration of ergonomics into an SPL increases productivity by providing the necessary tools which make it possible to replicate the procedure in other production areas or sectors.